Interdisciplinary Training-Human for Undergraduate Interdisciplinary Students and Members of the Federico Arango Foundation - Gallego Monsalve, Carlos Alberto (2021)
The objective of this text is to socialize briefly the significant experience of Interdisciplinary - Human Formation for Undergraduate Students and Members of the Federico Arango Foundation, an exercise developed with the Cultivation of Life Semillero belonging to the Faculty of Theology and Humanities in the Religion and Culture Line. This objective is articulated to the formative proposal of the Universidad Católica de Oriente that focuses its formation processes in "the service to the human person and the community" (Development Plan UCO 2018...). This exercise is evident in the training of students in their disciplines, with the transversality of humanism, thus strengthening the knowledge - to know, to know - to do and to know - to be. Humanisms that are based on the thought of Monsignor Alfonso Uribe Jaramillo, who proposes to do the axiological in a praxis from the Christian human perspective. This is how the Interdisciplinary-Human Formation Project for Undergraduate Students and Members of the Federico Arango Foundation was born, from the university environment, with its academic discussions, developing the practical proposal in a given social context.Work that, from the axiology becomes praxis with the methodology of Action Research, generating in the students of the University formative academic spaces that are shared with the members of the Foundation, with the purpose of taking to them, an incentive of why and for what to retake processes of change.